2020
DOI: 10.21585/ijcses.v4i2.96
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking Skills, Programming Self-Efficacies and Programming Attitudes of the Students

Abstract: The purpose of this research is to examine Computer Programming Attitude (CPA), Computer Programming Self-Efficacy (CPSE) and Computational Thinking (CT) skills of middle school students who took the Information Technologies & Software (IT&S) courses and those who did not, and make various analyses according to the relationships between these variables. As a result of the analysis, it was found that CPA and CPSE variables are significant predictors for CT skills, both students who took IT&S course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, the grade of the student also affected their CT and PSE. Günbatar's (2020) examination of learner CTS and PSE also found that computer PSE was a significant predictor of CTS. Similarly, Yildiz and Gündüz (2020) found that peer instruction increased student PSE perceptions in computer programming classes better than traditional instruction methods.…”
Section: Literature Review Computational Thinking (Ct)mentioning
confidence: 85%
“…Interestingly, the grade of the student also affected their CT and PSE. Günbatar's (2020) examination of learner CTS and PSE also found that computer PSE was a significant predictor of CTS. Similarly, Yildiz and Gündüz (2020) found that peer instruction increased student PSE perceptions in computer programming classes better than traditional instruction methods.…”
Section: Literature Review Computational Thinking (Ct)mentioning
confidence: 85%
“…This finding showed that students could improve their abstraction and decomposition skills even without learning any programming. In the study conducted by Günbatar (2020), it was found that middle school students who took the Information Technologies & Software (IT&S) course and learned programming had significantly higher CT skills than those who did not take the course. The development of students' CT skills after they are exposed to programming courses is actually expected.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined students' domain-specific CT skills (computer science or programming) in different contexts. (Erümit et al, 2020;Günbatar, 2020;Korucu et al, 2017;Oluk et al, 2018;Oluk & Korkmaz, 2016;Wu & Su, 2021) However, little is known about how the programming skills acquired from different programming environments change their domain-general CT skills; whether there is a difference between the domain-general CT skills of students who gain programming skills and those who do not especially in middle school. For this reason, two purposes were adopted in the study.…”
Section: Introductionmentioning
confidence: 99%
“…There is also extensive evidence that problem-solving skills (PSS) and computational thinking (CT), and computer programming are highly connected endeavors (Günbatar, 2020;Ozturk, 2021). Interestingly, these studies unified comments that traditional books do not work in academic learner success (quality).…”
Section: Regression Analysis Multicollinearitymentioning
confidence: 99%